(untitled) (CAHIERS MAGELLANES-NS, 2024)
In order to build a nation, the sector of Education is highly essential. To metamorphose India to a vibrant knowledge society, the New Education Policy (NEP) 2020 has marked an epoch-making development. The NEP, 2020 is the replacement of NEP, 1986 and brings a revolutionary change in all the dimensions of education emphasizing the importance on education technology in India. The NEP2020 throws some light on holistic education, skill-based education, creating innovation, vocational training and so on. In this study, an attempt has been made to discuss students’ perception towards NEP 2020 in Assam and implementing ICT tools in Classrooms and to identify the important factors for students’ benefit in implementing NEP 2020. In this regard, the data are collected from various colleges of Assam. The students who were enrolled in the 1st semester of four-year NEP courses are considered here for the research. A part from that, various statistical tools are used to study the aforesaid variables. The analysis is done by using computer software.